The Interplay between the ICC and Other International Courts and Tribunals: from the Nuremberg Principles to the Latest ICJ Case-Law - Šmigová, Katarína (The ICC at 25: Lessons Learnt, 2025)
This chapter explores the interplay between the International Criminal Court (ICC) and other international judicial bodies, notably the International Court of Justice (ICJ), through the lens of the foundational Nuremberg Principles. Originating from the Nuremberg trial after World War II, these principles presented revolutionary concepts under international law such as individual criminal responsibility, irrelevance of official capacity, and the precedence of international over national law. The analysis examines how these principles were adopted, adapted, or reinterpreted across the statutes and jurisprudence of subsequent international tribunals, including the ad hoc tribunals for Yugoslavia (ICTY) and Rwanda (ICTR), and also the Rome Statute, which established the ICC in 1998.The chapter marks out two key aspects of interplay: a developmental aspect, tracing the historical and legal evolution of the Nuremberg principles into contemporary instruments of international criminal justice; and an actual asspect, analysing the formal and practical application (or omission) of these principles in case law, particularly within ICC proceedings and ICJ advisory opinions. While the ICC does not formally treat the Nuremberg principles as binding legal sources under Article 21 of the Rome Statute, their normative influence remains evident.Special attention is paid to legal concepts such as immunities, complementarity, control over crimes, and fair trial rights, showing how these have been shaped by precedents across tribunals. The chapter also explores how the ICJ, despite focusing on state responsibility, has indirectly influenced ICC interpretations of international law through decisions like the Arrest Warrant and Genocide cases.At last, the chapter argues that the Nuremberg legacy continues to underpin the global criminal justice architecture, shaping the aim of upholding accountability, justice, and the rule of law. The dynamic relationship between courts underscores the interconnectedness of international efforts to prevent impunity and ensure human rights protections. Keywords: Nuremberg principles, International Criminal Court, international judicial bodies, interplay, sources of international (criminal) law